Գրիգոր Լուսավորչին վերագրվող տեսիլ-հարցումը - Պետրոսյան, Էսթեր
The present article scrutinizes an under-explored example of apocalyptic literature in the Armenian tradition: the Revelation attributed to Saint Gregory the Illuminator. The Revelation can be classified as a typical apocalyptic text, one conforming to the Society of Biblical Literature’s (SBL) taxonomy of such a text. It has a revelatory narrative, involving a divine figure, the angel, with whose help St. Gregory discloses a transcendent reality. The dating of the Revelation is still uncertain, as is the conjecture that it was translated from Syriac. This article contains a comprehensive examination of the existing scholarship concerning Gregory’s Revelation followed by a comparative edition of the text. This edition relies on the oldest known surviving manuscript, dating back to the year 1208. Статья посвящена одному из мало исследованных памятников апокалиптической литературы в армянской традиции – откровению, приписываемому святому Григорию Просветителю. Это типичный апокалиптический текст, подходящий под критерии, установленные Обществом библейской литературы (SBL). В откровении среди действующих лиц присутствует бесплотное существо, ангел, с помощью которого святой Григорий раскрывает тайны потустороннего мира и узнает, что происходит с душой после смерти. Вопрос о датировке откровения по сей день не решен. Филологам предстоит также установить, верна ли гипотеза о том, что «Откровение Григория» было переведено с сирийского языка. Статья включает в себя обзор литературы по теме исследования, а также критический текст откровения. Издание текста основано на самой ранней сохранившейся рукописи, датируемой 1208 годом.
Keywords: Հրապարակումներ; Գրիգոր Լուսավորիչ